Population genetics of forest type of Trypanosoma congolense circulating in Glossina palpalis palpalis of Fontem in the South-West region of Cameroon - Gustave Simo; Pythagore Soubgwi Fogue; Tresor Tito Tanekou Melachio; Flobert Njiokou; Jules Roger Kuiate; Tazoacha Asonganyi (Parasites & Vectors, 2014)
Abstract Background Genetic variation of microsatellite loci is a widely used method for the analysis of population genetic structure of several organisms. To improve our knowledge on the population genetics of trypanosomes, Trypanosoma congolense forest and savannah types were identified in the mid-guts of Glossina palpalis palpalis caught in five villages of Fontem in the South-West region of Cameroon. From the positive samples of Trypanosoma congolense forest, the genetic diversity and the population genetic structure of these parasites were evaluated. Method For this study, pyramidal traps were set up during three entomological surveys and 3347 tsetse flies were collected, dissected and 1903 midguts collected. DNA was extracted from midguts and specific primers were used to identify Trypanosoma congolense forest and savannah. All Trypanosoma congolense forest positive samples were characterized with seven microsatellite markers. Results Microscopic examination revealed 25 (1.31%) mid-gut infections with trypanosomes while the PCR method identified 120 (6.3%) infections due to Trypanosoma congolense: 94 (78.33%) Trypanosoma congolense forest and 28 (21.77%) Trypanosoma congolense savannah. The trypanosome infection rates varied significantly between villages and years of capture. Menji recorded the highest infection rate (15.11%); and samples captured in 2009 were more infected (14.33%). The microsatellite markers revealed a genetic variability between Trypanosoma congolense forest populations of Fontem villages and 6.38% of mixed infections due to different genotypes of T. congolense “forest type”. Conclusion Our data on the population genetics play in favor of a clonal reproduction of this parasite. The microsatellite markers used here showed a low genetic differentiation and an absence of sub-structuration (FST ≤ 0.0003) between Trypanosoma congolense forest populations of Fontem villages. However, the high FST value (FST ≥ 0.3911) between samples of the Democratic Republic of Congo and those of Fontem villages indicates low migration rates between trypanosomes of these subpopulations.